Educação CTS em livros didáticos: da análise à aproximação com a modelagem matemática - Cambi, Betina (2015)
This research proposes to conduct an analysis of high school mathematics textbooks in STS education perspective, with goal of to identify possible relationships with Mathematical Modeling. In addition, we sought to reflect how the CTS approach in textbooks can contribute to the development of Mathematical Modeling. This is considered as relevant to the educational context discussion, because there are little researchs in the area that discusses the possible relationships between STS education, mathematics and mathematical modeling. For this, the methodological procedures will be based on qualitative research. Data collection will be based in the documentary research, since the research is to analyze textbooks. Already the data analysis is characterized by a content analysis. Expectations with respect to satisfy the research objectives relate to possible changes in the context of the role of mathematics in social context, to try to promote the appreciation of conception of mathematical as tool for understanding the interrelationships between political, economic , technological and scientific. Furthermore, it is expected that, in establishing the possible relationships between the CTS Education and Mathematical Modeling, new paths open to the research and reflections in these areas.